FRI0358 99MTC-RHANNEXIN V-128 as a novel early diagnostic marker for interstitial lung disease associated with systemic sclerosis. (15th June 2017) - Guo, L; Schniering, J; Schibli, R; Blanc, A; Chicco, D; Ye, S; Distler, O; Béhé, M; Maurer, B
Abstract : Background: Interstitial lung disease (ILD), the primary cause of death in systemic sclerosis (SSc), often occurs early in the disease course, yet only becomes symptomatic when there is already substantial functional impairment and morphologic changes. Thus, there is an unmet need for early diagnosis. Apoptosis is considered the first pathophysiologic event in SSc-ILD. Monitoring of apoptotic processes with nuclear imaging, a sensitive, specific and noninvasive methodology, might be a promising new approach for the diagnosis of early SSc-ILD. Objectives: To evaluate the radiotracer 99m Tc-rhAnnexin V-128, which specifically targets a pathophysiologic key molecule of early apoptosis, for the detection of earliest stages of lung involvement in animal models of SSc-ILD with single photon emission computed tomography (SPECT/CT). Methods: C57BL/6J mice were treated with a single intratracheal injection of bleomycin or saline. Animals were euthanized at days 3, 7, 14 and 21 post-injection (n=6). Lung injury was evaluated by analysis of HE and Sirius red staining. The Ashcroft score was applied for the semi-quantitative evaluation of fibrotic changes. Immunofluorescence using the TUNEL assay and double staining with specific cell markers were performed to determine apoptotic cells. Positive nuclei were quantified by manual and automatic counting with Image J analysis software. Three days after injection with bleomycin or saline, mice were injected with 99m Tc-rhAnnexin V-128 (Advanced Accelerator Applications, Italy). After 1h, images were acquired using small animal SPECT/CT, followed by ex vivo autoradiography. Results: In the model of bleomycin-induced lung fibrosis, inflammatory infiltrates (CD45+) occurred as early as day 3 with peak at day 7, whereas pulmonary fibrosis developed from day 7 as assessed by Sirius red staining and was most pronounced at day 21 (mean Ashcroft score=4.6, p =0.0286). Notably, the number of apoptotic cells evaluated by TUNEL staining, was highest at day 3 (mean ± SE=6.5±1.5positive cells/HPF, p =0.0436) compared with saline controls (mean ± SE=0.7±0.1, p =0.0095) and then decreased over time. To determine the type of apoptotic cells, we performed immunofluorescent co-stainings with different cell markers. Data displayed that endothelial cells (vWF+) and epithelial cells (cytokeratin+), but not inflammatory cells (CD45+) were the primary cells undergoing apoptosis in earliest inflammatory stages of ILD. In accordance with the findings on tissue level, at day 3 post-injection, we detected ex vivo with autoradiography, yet not with in vivo SPECT/CT, an increased pulmonary uptake of 99m Tc-rhAnnexin V-128 in the lungs of bleomycin-induced mice compared with saline treated controls. Conclusions: Apoptosis of epithelial and endothelial cells preceded the development of pulmonary inflammation and fibrosis in the model of bleomycin-induced lung fibrosis. Thus, the use of 99m Tc-rhAnnexin V-128 might be a promising approach for the diagnosis of earliest stages of ILD. However, sensitivity of in vivo imaging has to be further improved. Disclosure of Interest: L. Guo: None declared, J. Schniering Grant/research support from: Swiss National Science Foundation (S-85605–02–01), R. Schibli: None declared, A. Blanc: None declared, D. Chicco Employee of: Advanced Accelarator Applications, S. Ye: None declared, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi;patent licensed mir-29 for the treatment of systemic sclerosis, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha, M. Béhé: None declared, B. Maurer Grant/research support from: AbbVie, Protagen, EMDO, Novartis, Pfizer, Roche, Actelion. Patent licensed: mir-29 for the treatment of systemic sclerosis